Highly active absorbent for SO2 removal prepared from coal ash (Part 2). - Magpantay, C.G (Philippine Engineering Journal)
This paper is a sequel of previous study (Part I) on the preparation of highly active absorbents for SO2 removal from coal ash and limestone. The prepared absorbent from coal fly ash was tested for its desulfurization activity at varying conditions using the experimental SO2 absorption analyzer. Simulated flue gas moisture used was composed of SO2, NO, CO2, O2 and H2O. The activity of the produced absorbent closely depends on the method of preparation taking into account the effect of time and temperature for curing and drying. The effects of particle size, surface area and percent glass content were correlated with the SO2 removal efficiency. The produced absorbent exhibited high efficiency not only for SO2 but also for NO removal at temperatures ranging from 100-165 degree celcius of the gas mixture. No serves as catalyst in the oxidation of SO2 to SO2 forming ettringite [Ca6Al2(SO4)3(OH)1225H2O or 6CaOAl2O33SO331H2O) and CaSO4 in the spent absorbent.